The ordo of care: A hermeneutical dialogue between Gordon Lathrop's liturgical theology and practices of care in the Open Church of Our Lady, Trondheim. (2nd January 2016) - Gunnes, Gyrid
Abstract : What is the relationship between practices of care towards people living in marginalized life situations and liturgy? This article addresses this question by exploring the liturgical theology of Gordon Lathrop as the theoretical starting point for analysing a practice that would conventionally not be described as "liturgy", but "ethical practice". At the heart of the liturgical theology of Lathrop is the idea that the ordo of the Sunday service is organized by juxtapositions and broken symbols. In this article, Lathrop's theology is brought into a hermeneutical dialogue with empirical material constructed from the Church of Our Lady, Trondheim, Norway, a Lutheran medieval church located in the middle of the city of Trondheim. Since 2008, the church has been run by the Church City Mission as an open church for all who need an open and hospitable sacred space in the city centre, especially people who live in marginalized life situations. The article demonstrates that when working inductively with an empirical material, Lathrop's concepts are too narrow and hermeneutically closed. In order to be theoretically sensitive to the experiences of people who live in marginalized life situations and the ethical practices of care, liturgical theology has to reimage its understanding of space.